Hedges and Boosters in Indonesian Scientific Articles - Triyoko, Hanung; Wijana, I Dewa Putu; Baryadi, I Praptomo (UIN Salatiga, 2021)
Hedging and boosting or ‘pembentengan’ (Indonesian) is the act of scientific writers in maintaining smooth scientific communication. This paper answers two problem formulations, i.e., what are the linguistic manifestations of hedges and boosters in Indonesian scientific articles, and how their meaning reveals the writer's level of confidence in the information conveyed. This study aims to enrich the description of scientific writing practices in Indonesia to support the development of scientific writing skills in general. This research uses descriptive qualitative methods. This research data is in the form of sentences containing hedges and boosters from various scientific journals published in Indonesia through the note-taking technique. The main theory to analyze the data is the theory on hedges and boosters. The data were analyzed semantically, syntactically, and pragmatically. The results show that hedges and boosters in the form of adverbs are the most commonly used in Indonesian Scientific writing. The meaning of hedges and boosters cannot always be determined by their lexical meaning because each hedge and booster has to be seen in its use in the sentence. The Indonesian scientific community has its own agreement in the social interaction of scientific articles.Keywords: scientific writing; hedges and boosters; confidence; doubt; function; interaction